Mitigating the COVID-19 effect: Emergency economic policy-making in Central Europe - Ana Podvršič; Joachim Becker; Dóra Piroska; Tomáš Profant; Vladan Hodulák (European Trade Union Institute (ETUI), 2020)
The paper analyses the economic policy-making in the first phase of the epidemic in five Central Europe countries, Austria, Czechia, Hungary, Slovakia and Slovenia, whose economic structure is characterized by strong export orientation. We focus on the participatory character of the governments' COVID-19 packages, on their design, and targets. We find that while social actors were selectively integrated in the policy-making, depending on the established tripartite framework and government political composition, support packages deployed similar tools (such as short-time work provisions, loan and guarantee programmes through development banks, tax/security payment deferrals) though with varying weight and scope. Only in Austria and Czechia the governments adopted specific measures for the export sector. We also find that the scope of the fiscally immediately relevant measures is rather limited, resulting in lesser loan programs and social provisions. Although the budgetary limitations have been temporarily suspended by the European Union, the governments in the periphery, regardless of their political inclinations, remain constrained by their uneven integration into the EU's single market, as well as by their limited access to international financial markets.
Keywords: 330; coronavirus; Economic crisis; economic policy; export economy; foreign trade policy; Central Europe; Austria; Hungary; Czech Republic; Slovakia; Slovenia; Coronavirus; Wirtschaftskrise; Wirtschaftspolitik; Exportwirtschaft; Außenwirtschaftspolitik; Vergleich; Mitteleuropa; Österreich; Ungarn; Tschechien; Slowakei; Slowenien